Business rates in multi-occupied properties : Consultation on reinstating the practice of the Valuation Office Agency prior to the decision of the Supreme Court in Woolway (VO) v Mazars [2015] UKSC 53.: Consultation on reinstating the practice of the Valuation Office Agency prior to the decision of the Supreme Court in Woolway (VO) v Mazars [2015] UKSC 53. (December 2017) - Great Britain., Department for Communities and Local Government
No abstract available